The Implementation of English for Specific Purposes (ESP) in Improving Students Speaking Skill of UKI Paulus Makassar - Luana Sasabone; Yuriatson Jubhari; Sukmawati; Sujarwo (CV. Eureka Murakabi Abadi, 2021)
Communicative speaking skill is considered the most essential skill for everyday situations and for a wide range of professions especially in the economic and business sector. The purpose of this research is to improve students speaking skill of UKI Paulus Makassar through the implementation English for Specific Purposes (ESP). This study used Classroom Action Research (CAR) namely (1) planning, (2) actions, (3) observation, and (4) reflection. For the purpose of the topic, 35 students were selected as the subject. Research method was Classroom Action Research (CAR) with Kemmis and Taggart model. It was conducted for about two cycles namely cycle I and cycle II. According to the results of speaking test, findings showed that the implementation English for Specific Purposes (ESP) in teaching had positive meaningful effect on improving students’ speaking skill after being obtained test results both cycle 1 and cycle II in Economic and Business students of UKI Paulus Makassar